THE EFFECT OF SUSTAINABILITY REPORT DISCLOSURE AND CORPORATE GOVERNANCE ON FIRM PERFORMANCE WITH AUDIT QUALITY AS A MODERATION - Naibaho, Eduard Ary Binsar; Ekarandi, Felix (Universitas Bunda Mulia, 2025)
Background: In the face of economic uncertainty and increasing demands for transparency, companies are required to improve performance through the implementation of sustainability reporting, corporate governance, and maintaining audit quality to build investor and stakeholder trust.Objective: This study aims to test the influence of these three factors on firm performance in Indonesia, considering the limited number of studies that discuss the three simultaneously in the context of Indonesian companies across sectors.Research Methods: Using secondary data from financial and annual reports of Indonesian companies between 2019 and 2023, a purposive sampling technique was applied. Data analysis involved quantitative methods to test hypotheses through statistical models.Research Results: The results indicate that corporate governance mechanisms, particularly ownership concentration and board size, negatively influence firm performance. Sustainability reporting positively affects performance, and audit quality strengthens the relationship between sustainability report disclosure and firm performance.Originality/Novelty of Research: This research contributes to the existing literature by highlighting the significant role of sustainability and governance practices in enhancing firm performance in the Indonesian context, and by exploring the moderating effect of audit quality, which has been less studied.